Isolation and selection of Dehalogenating Bacteria from soils = Isolasi dan seleksi Bakteri Dehalogenasi dari tanah - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 1991)
Pseudomonas sp. and Arthrobacter sp. isolated from forest soil by enrichment culture were able to utilize monochloroaceticacid as sole Carbon and energy sources. The ability to utilize a range of halogeneted compounds was conferred by a single halidohydrolase type dehaÂ¬logenase. The presence of the enzyme in cell-free extracts was demonstrated by activity coomasie blue stain polyacrylamide gel electrophoresis